Hermit crabs from Brazil: Family Diogenidae (Crustacea: Decapoda: Paguroidea), except Paguristes - Nucci, Paulo Ricardo; de Melo, Gustavo Augusto Schmidt (Zootaxa, 2015)
We present here the genera and species of the family Diogenidae recorded from Brazil, with the exception of the genus Paguristes. We provide a diagnosis, synonymy and illustrations for each species of the nine genera from Brazil and identification keys for genera represented by more than one species.